Surgical Management Of Radicular Cyst : A Case Report With Histopathological Confirmation - Erli Anatta; Mahfuzi El Haris (International Journal of Health Engineering and Technology, 2026)
Radicular cysts are the most common inflammatory odontogenic cysts found in the jaws, accounting for approximately 52–68% of all jaw cysts. These lesions originate from the proliferation of epithelial rests of Malassez in the periodontal ligament, triggered by chronic periapical inflammation due to pulp necrosis. Due to their slow-growing nature and often asymptomatic presentation, these cysts frequently reach a significant size before being clinically detected. This case report describes a 48-year-old male patient who presented to Soelastri Dental and Oral Hospital, Surakarta, with a chief complaint of a retained root in the lower left posterior region for approximately three years. The patient reported a prior history of pain that had been self-managed. Clinical examination revealed a retained root in tooth 35 (FDI notation), with positive palpation and negative percussion findings. Periapical radiography showed a well-defined unilocular radiolucency with a sclerotic cortical border, measuring approximately 4 × 3 mm in the periapical region. Surgical management was performed under inferior alveolar nerve block and infiltration anesthesia. A triangular mucoperiosteal flap was elevated, followed by alveolar bone reduction, radiks extraction, cyst enucleation, thorough curettage, and placement of a hemostatic sponge. Primary wound closure was achieved using 4-0 silk sutures. In conclusion, histopathological examination confirmed the diagnosis of a radicular cyst, characterized by stratified squamous epithelial lining and chronic suppurative inflammation within the fibrous capsule. A two-week postoperative follow-up showed good mucosal healing without complications. This case highlights the importance of integrating clinical, radiographic, and histopathological evaluations for accurate diagnosis and appropriate surgical management of radicular cysts associated with retained roots